2021
DOI: 10.1016/j.dld.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus gastritis: Clinicopathological profile

Abstract: Background: Cytomegalovirus (CMV) gastritis is occasionally reported in case reports and limited case series. Up to now, it is the largest and most comprehensive retrospective study of CMV gastritis. Methods: All patients who were histologically diagnosed with CMV gastritis at Linkou Chang Gung Memorial Hospital between January 20 0 0 and April 2020 were included. Patients were divided into two groups according to immunity. Between-group differences in characteristics, manifestations, endoscopic features, prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…The two latest retrospective studies that enrolled 213 and 173 patients with positive H&E or IHC staining in Thailand found that antiviral treatment was the only protective factor that improved patient survival [7,9]. However, in our previous studies on CMV gastritis, enteritis, and colitis, antiviral therapy had no significant impact on in-hospital survival [8,14,15].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The two latest retrospective studies that enrolled 213 and 173 patients with positive H&E or IHC staining in Thailand found that antiviral treatment was the only protective factor that improved patient survival [7,9]. However, in our previous studies on CMV gastritis, enteritis, and colitis, antiviral therapy had no significant impact on in-hospital survival [8,14,15].…”
Section: Introductionmentioning
confidence: 67%
“…Patients were defined as "immunocompromised" if they were recipients of solid organ or hematopoietic stem cell transplant or were documented to have primary immunodeficiency, human immunodeficiency virus infection, exposure to chemotherapeutic agents or radiotherapy within the last 6 months, and/or use immunosuppressants (including corticosteroids (oral or intravenous administration, ≥20 mg/day of prednisolone or any equivalent for >2 weeks)) [8,14,15].…”
Section: Definition Of Immune Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV enteritis is a rare but fatal disease that has been under diagnosed. It is not only an opportunistic infection in immunocompromised patients, but also affects immunocompetent individuals [ 2 , 3 , 10 , 14 ]. Despite the development of small intestinal endoscopies, such as capsule endoscopy, single-balloon enteroscopy, and double-balloon enteroscopy, diagnosis of CMV enteritis is still difficult due to critical general condition of the patients, various clinical presentations, and expensive procedure fees.…”
Section: Discussionmentioning
confidence: 99%
“…It causes not only subclinical infections but also serious tissue invasive diseases. The gastrointestinal (GI) tract is a common location for CMV infection, both in immunocompromised as well as immunocompetent patients; it has variable clinical presentations and a high mortality rate [ 2 5 ]. Research of small intestinal CMV disease is relatively rare compared to other GI tract CMV diseases possibly due to difficult tissue sampling.…”
Section: Introductionmentioning
confidence: 99%